Central auditory processing is altered after traumatic brain injury in Tanzanian adults - Lichtenstein, Jonathan D.; Niemczak, Christopher E.; Fellows, Abigail; Wood, Lindsay J.; Masoud, Shufaa; Rooney, Alexis; Adhikari, Monika; Magohe, Albert; Buckey, Jay C. (Frontiers in Neuroscience, 2025)
Traumatic brain injury (TBI) damages pathways throughout the brain and is a significant global health concern, particularly in low- and middle-income countries, where the incidence is high and long-term deficits are prevalent. This study explores the utility of central auditory processing (CAP) testing as a marker of previous TBI. Seventy individuals with a history of moderate to severe TBI (msTBI) were matched by age and sex to 46 healthy controls in Dar es Salaam, Tanzania. Participants underwent comprehensive behavioral CAP testing, including tests of speech-in-noise ability, temporal resolution, and dichotic listening. Multivariate logistic regression showed the Triple Digit Test (TDT) (p < 0.001) significantly predicted msTBI status, independent of age and peripheral hearing ability. Elastic net modeling supported these findings, highlighting TDT performance as the most robust predictor of msTBI history. A history of msTBI is associated with poorer CAP performance, particularly on speech-in-noise tests. These tests could serve as accessible, resource-efficient tools for assessing brain function related to TBI in clinical and resource-limited settings. Studies in larger, more diverse populations are needed to explore their predictive utility for long-term cognitive outcomes after TBI.